O Crédito na Banca Europeia e os Requisitos de Capital e Liquidez de Basileia III. - Rodrigo Borges Teixeira (2019)
Due to the 2008 crisis, the Basel Committee established new risk-weighted capital requirements and short and long-term liquidity instruments to increase the efficiency, stability and resilience of the banking sector. Most of the scientific literature states that, as a consequence of Basel III, there was a reduction of the GDP and a credit withdrawal in the economy, but also a reduction of the probability of systemic crisis and a bigger stability of the banking sector and of the economy. This study analyses the impact of the capital and liquidity's requirements of Basel III on credit activity and on the possibility of crisis. The analysis was based on information from several banks from 28 European countries, regarding the period from 2014 to 2017. Different econometric methods were used, one was the PROBIT model, to estimate the probability of a credit crisis and to identify its explanatory factors, and the other was the method of moments for panel data with individual effects, to estimate the impacts on the bank loans and to empirically validate their determinants. Most of the results present positive relationships between the Basel III requirements and bigger economic and credit activity stability. The separation of banks in small, medium and big also reveals asymmetric answers in the main study variables, so the definition of differentiated policies could improve the system's efficacy.